Divine Simplicity, Aseity, and Sovereignty - Baddorf, Matthew (Sophia, 2017)
The doctrine of divine simplicity has recently been ably defended, but very little work has been done considering reasons to believe God is simple. This paper begins to address this lack. I consider whether divine aseity (the traditionally prominent motivation) or the related notion of divine sovereignty provide us with good reason to affirm divine simplicity. Divine complexity has sometimes been thought to imply that God would possess an efficient cause; or, alternatively, that God would be grounded by God's constituents. I argue that divine complexity implies neither of these, and so that a complex God could also exist a se. Similarly, a complex God might be thought less sovereign than a simple God, due to lacking control over the divine constituents. I argue in reply that a complex God either has just as much control as a simple God, or that a complex God's relative lack of control should cause no theological problems. The upshot is that neither the doctrines of divine aseity or of divine sovereignty give theists good reason to endorse divine simplicity.